2010
DOI: 10.1155/2010/263593
|View full text |Cite
|
Sign up to set email alerts
|

Emotion on the Road—Necessity, Acceptance, and Feasibility of Affective Computing in the Car

Abstract: Besides reduction of energy consumption, which implies alternate actuation and light construction, the main research domain in automobile development in the near future is dominated by driver assistance and natural driver-car communication. The ability of a car to understand natural speech and provide a human-like driver assistance system can be expected to be a factor decisive for market success on par with automatic driving systems. Emotional factors and affective states are thereby crucial for enhanced safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 54 publications
0
82
0
Order By: Relevance
“…Previous attempts have successfully captured mostly negative valence in various driving conditions [25]. Considering that the high relevance of positive valence to driving was documented by a substantial body of literature [7], future DSM systems could benefit from detection of positive emotions. Therefore, specific scenario mode was designed to elicit positive emotion onto participating drivers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts have successfully captured mostly negative valence in various driving conditions [25]. Considering that the high relevance of positive valence to driving was documented by a substantial body of literature [7], future DSM systems could benefit from detection of positive emotions. Therefore, specific scenario mode was designed to elicit positive emotion onto participating drivers.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, presence of extensive emotions, especially anger, can make a driver prone to errors and could lead to dangerous driving [6]. Joy or happiness, on the other hand, could be beneficial to driving [7]. Therefore, it is important to equip future vehicles with an onboard system capable of tracking and analysing driver state to be able to mitigate the risk of incorrect vehicle control prior to its actual occurrence, which subsequently has a potential to reduce the number of human error related road accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Perspectives and the Role of Consumer Electronics* Happiness, on the other hand, could be beneficial to driving [19]. Clearly, the evidence shows that until a human remains in full or partial control of a vehicle, drivers' state is an important aspect of driving and cannot be neglected due to its critical influence.…”
Section: Towards Hybrid Driver State Monitoring: Review Futurementioning
confidence: 99%
“…Current research and attention theory have suggested that speech-based interactions are less distracting than interaction with visual display [12]. A careful design of effective speech interface can also be potential aid for a drowsy driver [13], [14]. However, [15] suggests that the only safe countermeasure against driving while sleepy is to stop driving.…”
Section: Auditory Cues During Drivingmentioning
confidence: 99%